Induction of RNAi Core Machinery’s Gene Expression by Exogenous dsRNA and the Effects of Pre-exposure to dsRNA on the Gene Silencing Efficiency in the Pea Aphid (Acyrthosiphon pisum) - Ye, Chao; An, Xin; Jiang, Yi-Di; Ding, Bi-Yue; Shang, Feng; Christiaens, Olivier; Taning, Clauvis Nji Tizi; Smagghe, Guy; Niu, Jinzhi; Wang, Jin-Jun (Frontiers in Physiology, 2019)
The pea aphid, Acyrthosiphon pisum, is an important agricultural pest and biological model organism, and RNA interference (RNAi) is an important tool for functional genomics and for insect pest management. However, the efficiency of RNAi in pea aphids is variable, limiting its application in aphids. In this study, we present optimized conditions for inducing and increasing the gene silencing efficiency of RNAi in pea aphids. The optimal gene silencing of the target Aphunchback gene was achieved by injecting 600 ng double-stranded (ds) RNA, and the highest mRNA depletion rate (74%) was detected at 36 h after injection. Moreover, the same gene silencing conditions were used to achieve transcript silencing for nine different genes in the pea aphid, although the silencing efficiencies for the different genes varied. Furthermore, the pre-exposure of aphids to dsRNA (600 ng dsGFP) led to significant hunchback silencing following a secondary exposure to 60 ng of dshunchback, a dose which did not lead to gene silencing when independently injected. The information presented here can be exploited to develop more efficient RNAi bioassays for pea aphids, both as gene functional study tools and an insect pest control strategy.